ANALISIS KOMPARASI PENDAPATAN USAHATANI SALAK PONDOH PADA LAHAN MILIK PETANI DENGAN LAHAN MILIK PERHUTANI DI DESA KAJEKSAN KECAMATAN SUKOHARJO KABUPATEN WONOSOBO - Rahazu Puji Astuti; Bambang Mulyatno Setiawan; Edy Prasetyo (Universitas Tadulako, 2020)
The purposes of this research was to compare income and value of R/C Ratio of salak Pondoh farming systems belong to people plantation and Perhutani; and to analyze the feasibility of salak Pondoh farmings on both systems in Kajeksan Village. The research was conducted in January - February 2019 in Kajeksan village Sukoharjo subdistrict Wonosobo regency. The research locations were purposively determined. Sixty respondent samples were selected using a quota sampling consisted of 30 farmer respondents and 30 respondents from Perhutani. Data was analyzed using quantitative analysis such as calculation of farming costs, revenue, income, and R/C ratio. The difference in income was determined using the independent sample t-test while the feasibility of the salak pondoh farming system used one sample t-test. The income generated from the people plantation (IDR 45,391,584) was significantly greater than that from Perhutani (IDR 21,011,333). The average R/C Ratio value of the people plantation (3.9) was also larger than that of Perhutani (2.7). However, both farming systems are feasible because both have the average R/C Ratio >1. Keywords: Comparison, Feasibility, Income, R/C Ratio, and Salak Pondoh.